Robert Ludlum's The Bourne shadow [large type] - Freeman, Brian, 1963-; Ludlum, Robert, 1927-2001 (Ludlum, Robert, 1927-2001. Jason Bourne series, 2024)
"It's been over a decade since Nash Rollins recruited David Webb to join Treadstone. Webb became the agent known as Cain--and later took on the identity of Jason Bourne. After the injury that erased Bourne's whole life, Nash lied about the circumstances of David's recruitment to Treadstone. He was afraid that learning the truth might drive Bourne out of the agency forever. But now, when Bourne meets a woman who recognizes him as David Webb, the secrets of those days begin to come out--and Bourne is forced to confront the dangerous ghosts of a past he doesn't even remember"--